Analysis of Students' Preferences for Digital Applications in the Context of Learning Spoken English among Private University Students in Banda Aceh - Nirwan, Nirwan; Helmanda, Cut Mawar; Nisa, Rahmatun (JETLi: Journal of English Teaching and Linguistics, 2023)
This study delves into analyzing student preferences regarding using digital applications in the context of English language speaking skills among undergraduate students at private universities in Banda Aceh. Based on a mixed-methods approach, the research explores the complex interplay between student preferences, the usage of digital applications, and the consequent language learning outcomes. Findings reveal diverse preferences among the student population, with a significant proportion favoring traditional classroom-based learning while a growing segment leans towards digital methods. The study also highlights the relationship between preferences and the extent of digital application utilization, shedding light on the factors influencing these choices. The research underscores the significance of accommodating diverse learning preferences in language education and acknowledges the potential of digital applications in enhancing speaking skills. It provides valuable insights for educators and institutions aiming to optimize language learning programs, ensuring a balanced and practical approach in the ever-evolving landscape of language education.